PROLAPSO DE VAGINA EM VACA HOLANDESA - Zientarski, Tainara Letícia; Pereira, Roberta Carneiro Da Fontoura; Müller, Matheus Borges (Salão do Conhecimento, 2019)
Relato Supervisionado da disciplina de Estágio Clínico I em Medicina Veterinária da UNIJUÍ.